PERAN UNITED NATION HIGH COMMSSIONER FOR REFUGEES (UNHCR) DALAM MENANGANI PENGUNGSI DI SPANYOL - Williadi Pratama; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study discusses “the role of the United Nations High Commissioner for Refugees (unhcr) in dealing with refugees in Spain”. many of the refugees who came to Spain were caused by the worsening conditions in their home countries such as natural disasters, economies, and war that forced them to leave their home countries and seek safer shelter in other countries and to save themselves from threatening dangers they. As a result of these problems, the UN refugee protection agency, the UN High Commissioner for Refugees, provides assistance to refugees in Spain.The method used in this study is qualitative explanative. This study uses secondary data using library research. This study uses the Perspective of Pluralism by Paul R, Viotti and Mark V. Kauppi, Level Analysis of Group Behavior, and Theories of international organizations by Clive ArcherThe result of this research is the role of the United Nations High Commissioner for Refugees in handling refugees in Spain is by conducting programs such as educational programs, fundraising, campaigns and working with the Spanish government. The programs run by the United Nations High Commissioner for Refugees are quite successful with many giving assistance to refugees in Spain